COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE OF CONVENTIONAL BANK AND SHARIA BANK IN INDONESIA: ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK KONVENSIONAL DENGAN BANK SYARIAH DI INDONESIA - Yusriwarti; Boni Kristoven; Dini Oktaviani; M. Ilham Tanjung; Prehasti Regita (Indragiri Research Center (ingreat), 2024)
This research aims to compare the financial performance between Conventional Banks and Sharia Banks in the 2019-2023 period in Indonesia. The samples from this research were BCA Bank as a Conventional Bank and BCA Syariah Bank as a Sharia Bank, and sampling was determined using the purposive sampling method. This research uses financial ratios in the form of Non Performance Financing (NPF), Financing To Deposit Ratio (FDR), Return on Assets (ROA), Operational Expenditure to Operational Income (BOPO), Capital Adequacy Ratio (CAR). This research uses the Independent Sample t-Test. The research results show that Bank BCA has ideal ratio values ​​for ROA, BOPO, CAR, whereas Bank BCA Syariah has ideal ratio values ​​for NPF, FDR and CAR. Overall or the average ratio, there is a significant difference between Conventional Banks and Sharia Banks.